Mayflowers and Sleeping Johnnies: Nature-Study, Local Knowledge, and A. H. MacKay’s Phenological Research in Rural Nova Scotia, 1892-1925 - Spike, Sara (Scientia Canadensis, 2020)
This article explores the social context of a crowd-sourced science experiment to record phenological data in early twentieth-century rural Nova Scotia, run through the provincial school system. It focuses in particular on the interaction between the project administrators and the rural people who participated, bringing non-traditional actors—young rural women and children—to the foreground of the history of science in Canada. These ongoing interactions reveal early twentieth-century efforts to consolidate scientific authority alongside efforts to standardize rural engagements with the natural world. However, participants challenged the project’s scientific ideals, asserting the relevance of local, place-based knowledge in rural Nova Scotia.